New insights into surface functionalization and preparation methods of MWCNT based semiconductor photocatalysts - Joseph, Honey Mary; Sugunan, S.; Gurrala, Lakshmiprasad; Mohan, Mothi Krishna; Gopi, Soumya (Ceramics International, 2019)
The manuscript primarily describes the influence of various synthesis strategies on the photocatalytic properties of MWCNT/TiO2 binary nanohybrids. The multiwalled carbon nanotube modified titania hybrids synthesized via two-step reaction involving the covalent functionalization with green and mild oxidizing agent like H2O2, followed by simple surfactant/template free hydrothermal synthesis exhibited the maximum photocatalytic efficiency. The Total Organic Carbon (TOC) analysis showed complete mineralization of the persistent Rhodamine B dye in about 8 h. These synthesized nanohybrids in varying MWCNT content were tested for their photocatalytic efficiency in the degradation of explosive effluents like 4-nitrophenol and picric acid. The UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS), X-ray photoelectron spectroscopy (XPS), Brunauer Emmett Teller Surface area analysis (BET), Fourier transform infrared spectroscopy (FT-IR), Transmission electron microscopy (TEM) and Raman spectra analysis evidently revealed the effective synergistic interaction between the MWCNT and titania at the interface that has contributed to the significant enhancement of photocatalytic performance.
Keywords: Functionalization; Multiwalled carbon nanotubes (MWCNTs); Nitrophenol (4-NP); Photocatalysis; Picric acid (PA); Rhodamine B (RhB); Sol gel and hydrothermal method; synergistic effects; Titania (TiO2); Total organic carbon content (TOC)